2016
DOI: 10.1097/iae.0000000000000997
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Morphologic Deterioration in Patients With Lamellar Macular Holes

Abstract: Multifocal electroretinography is a useful tool for predicting morphologic deterioration of LMHs. Lower multifocal electroretinography amplitudes in R1 and R2 predict an increased risk of subsequent deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…On the other hand, others have shown that LMH are not static entities and may undergo changes with time [ 15 , 108 , 111 ]. Theodossiadis and colleagues [ 108 ] reported that in their series of 41 eyes that were followed for a mean of 37 months with time domain OCT, 22% of eyes developed a decrease of visual acuity from baseline.…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, others have shown that LMH are not static entities and may undergo changes with time [ 15 , 108 , 111 ]. Theodossiadis and colleagues [ 108 ] reported that in their series of 41 eyes that were followed for a mean of 37 months with time domain OCT, 22% of eyes developed a decrease of visual acuity from baseline.…”
Section: Natural Historymentioning
confidence: 99%
“…Eyes were assessed with multifocal ERG and SD-OCT at baseline and at 12 months of follow-up. At 12 months of follow-up almost a third of LMH eyes experienced morphological deterioration, evidenced by a mean decrease of 10% in central retinal thickness [ 111 ].…”
Section: Natural Historymentioning
confidence: 99%
“…The 27 eyes which remained intact did not show significant difference from controls. Chung and colleagues 20 analyzed mfERG responses in eyes with lamellar MH and found that eyes with lower response amplitudes in rings 1 and 2 showed higher morphologic deterioration compared with eyes which maintained higher response levels in the same amplitudes. The current study, however, revealed significantly reduced retinal responses not only in the three eyes which developed an MH, but also in all the fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the error of the measured value [19][20][21], we defined the improvement in myopic retinoschisis as a decrease in the total retinal thickness by more than 10% in two or more out of five sections without an increase in volume of more than 10% in any other sections. The opposite case was considered an aggravation.…”
Section: Methodsmentioning
confidence: 99%